A subject analysis of the Pampanga High School Science Congress Research Papers from 1997 to 2018 using text mining - Balajadia, Princess Anne D.; Baluyut, Anna Desiree A. (School of Library and Information Studies, University of the Philippines Diliman, 2018)
This study was conducted to process the available research collection of the Pampanga High School (PHS) Special Science Class (SSC) Science Congress from 1997-2018 in able to determine the subject, and research trends through text mining, as well as to accommodate the need for easier access on navigation search, and retrieval of documents through an electronic database. Although a total of 607 blue books remain in the research room of PHS, only 458 of them are accessible and only 137 have corresponding electronics resources. The researchers utilized a descriptive research study to establish the subject and trends analysis of the research papers as well as the most accessed resources used by the students for their investigatory project. First, they listed down the elements needed such as the tittle, author/s, subjects of each research paper, and citations, which was then processed using the Statistical Package for the Social Sciences. Gathering 4,037 citations, the researchers found out that the most accessed type bibliographic resources are electronic resources, amounting to 2,383 entries, and followed by books and journals with 863 citations and 449 citations respectively. The most cited type of electronic resources is Wikipedia which took up 542 citations and is followed by Microsoft Encarta and wiseGEEK with 43 and 42 citations respectively. For the subjects, Plant Sciences came out on top at the frequency of 298, while Chemistry and Medicine followed with 176 and 84 respectively. It should also be noted that multiple subjects can be assigned to one research paper. On the other hand, the researchers utilized RStudio to mine the text in the 458 titles from the research collection. The term “production ” has the highest frequency count with 100 counts, which is followed by “leaves” with 67 counts, and “extract” with 62 counts. Both results show that the subjects of the research papers, are leaning towards life Sciences more. In classifying the research papers, the researchers devised their own classification scheme. The subjects were based on the classification used by the intel ISEF and were then translated into Dewey Decimal Classification Hundred/Thousand Division . In the formulation of the electronic database, the researchers utilized Greenstone, an open-source digital library software. The researchers then conducted a survey with 46 respondents about the usability of the database after the students tested it and performed a thematic analysis.